Macrophage‐derived insulin‐like growth factor‐1 is a key neurotrophic and nerve‐sensitizing factor in pain associated with endometriosis. Issue 10 (10th July 2019) - Forster, Rachel; Sarginson, Alexandra; Velichkova, Atanaska; Hogg, Chloe; Dorning, Ashley; Horne, Andrew W.; Saunders, Philippa T. K.; Greaves, Erin
ABSTRACT: Endometriosis is a common incurable inflammatory disorder that is associated with debilitating pelvic pain in women. Macrophages are central to the pathophysiology of endometriosis: they dictate the growth and vascularization of endometriosis lesions and more recently have been shown to promote lesion innervation. The aim of this study was to determine the mechanistic role of macrophages in producing pain associated with endometriosis. Herein, we show that macrophage depletion in a mouse model of endometriosis can reverse abnormal changes in pain behavior. We identified that disease‐modified macrophages exhibit increased expression of IGF‐1 in an in vitro model of endometriosis‐associated macrophages and confirmed expression by lesion‐resident macrophages in mice and women. Concentrations of IGF‐1 were elevated in peritoneal fluid from women with endometriosis and positively correlate with their pain scores. Mechanistically, we demonstrate that macrophage‐derived IGF‐1 promotes sprouting neurogenesis and nerve sensitization in vitro . Finally, we show that the Igf‐1 receptor inhibitor linsitinib reverses the pain behavior observed in mice with endometriosis. Our data support a role for macrophage‐derived IGF‐1 as a key neurotrophic and sensitizing factor in endometriosis, and we propose that therapies that modify macrophage phenotype may be attractive therapeutic options for the treatment of women with endometriosis‐associated pain.—Forster, R., Sarginson, A., Velichkova, A., Hogg, C., Doming, A., Home, A. W., Saunders, P. T. K., Greaves, E. Macrophage‐derived insulin‐like growth factor‐1 is a key neurotrophic and nerve‐sensitizing factor in pain associated with endometriosis. FASEB J. 33, 11210–11222 (2019). www.fasebj.org